The Relationship Between the Preoperative Neutrophil-to-Lymphocyte Ratio and Postoperative Nausea and Vomiting in Patients Undergoing Septorhinoplasty Surgery - Altun, Aysun Yildiz; Demirel, Ismail; Bolat, Esef; Ozcan, Sibel; Altun, Serdar; Aksu, Ahmet; Bestas, Azize (Springer, 2019)
Background Postoperative nausea and vomiting (PONV) is one of the most common complications during the postoperative period. In the literature, there are many factors associated with PONV risk, but it is claimed that inflammation increases this risk. The neutrophil-to-lymphocyte ratio (NLR) is a cheap parameter to use in the diagnosis and follow-up of systemic inflammatory diseases. In this study, we aimed to investigate whether the preoperative NLR was a marker for PONV and to determine its relation with antiemetic use. Methods Eighty patients who were planned to undergo elective septorhinoplasty and were in ASA I-II were prospectively included in the study. The NLR value was calculated by dividing the number of neutrophils by the number of lymphocytes obtained from the preoperative complete blood count. The patients were divided into two groups of 40 patients: patients with an NLR < 2 (group 1) and patients with an NLR >2 (group 2). Nausea and vomiting during the first 24h in the recovery room and in the related clinic and antiemetic requirement were recorded. Results The rate of nausea-vomiting in the recovery room and in the postoperative 24-h period in group 1 was significantly lower than in group 2 (p < 0.05). The rate of use of antiemetics in the recovery room and in the postoperative 24-h period in group 1 was significantly lower than in group 2 (p < 0.05). Conclusion NLR values above 2 calculated in the preoperative period may be an indicator of PONV risk. Antiemetic prophylaxis may be given according to this value.
Keywords: Postoperative nausea and vomiting; Neutrophil-to-lymphocyte ratio; Antiemetic